Self-rating depression during early postoperative period after colostomy following radical surgery for rectal cancer - Hao, Xue; Liying, Ma; Ming, Zhong; Shah, Jay (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Colorectal cancer (CRC) is 3rd most common cancer. Half of which requires colostomy. It leads to anxiety and depression with less than optimal quality of life. Zung Self-rating Depression Scale is a reliable tool used in Chinese population for identifying and addressing mental health status for appropriate education. The aim of this study is to investigate the depression state in rectal cancer patients after colostomy, then analyze its influence factors.Methods: A cross sectional study in rectal cancer patients who had colostomy after radical surgery for rectal cancer were investigated for depression during early postoperative period within one week using Zung’s self-rating depression scale (SDS). Multiple logistic regression analysis was done to identify the risk factor.Results: There were 55 colostomies patients (male 30 and female 25 patients, age 50.11+/-13.17 years) after rectal cancer surgery during the study period. The SDS score of was higher than national norm (P